Urban Climate Justice Theory, Praxis, Resistance - Rice, Jennifer L.; Long, Joshua; Levenda, Anthony (University of Georgia Press, 2024)
Arguing that climate injustice is one of our most pressing urban problems, this volume explores the possibilities and challenges for more just urban futures under climate change. Whether the situation be displacement within cities through carbon gentrification or the increasing securitization of elite spaces for climate protection, climate justice and urban justice are intimately connected. Contributors to the volume build theoretical tools for interrogating the root causes of climate change, as well as policy failures. They also highlight knowledge produced within communities already seeking transformative change and demonstrate meaningful learning from activist groups working to address the socionatural injustices caused by the impact of climate change. The editors' introduction situates our current climate emergency within historical processes of colonization, racial capitalism, and heteropatriarchy, while the editors' conclusion offers pathways forward through abolition, care, and reparations. Where other books focus on the project of critique, this collection advances real-world politics to help academics, practitioners, and social justice groups imagine, create, and enact more just urban futures under climate change.